Recent Developments in Chinese Urban Planning
XIII, 367 p. 208 illus.
Keywords: This book provides a comprehensive overview of the most recent development of Chinese cities. It discusses a broad range of subjects of urban planning, including environmental planning, transportation planning, historical preservation, economic development, geographic information systems (GIS) and other technological applications. China, the most populous country in the world, has experienced unprecedented urbanization in a relatively short period. During the past decades, urbanization in China has centered on land development through industrialization and investment, but it has largely ignored the prosperity and well-being of the people. Livable cities are not just those with magnificent buildings and infrastructure; they are great places where people want to live. China’s recently inaugurated leaders have proposed a new model to actively and prudently enhance the quality of urbanization through compact, intelligent, and low-carbon development. It symbolizes the departure from land-centered urban development to a form of people-oriented urbanization, as China’s Premier, Li Keqiang, has advocated. This new model offers a platform for planning researchers and practitioners to tackle urbanization challenges, such as social equity, environment, energy, ecological and historic preservation, affordable housing, and externalities of mega cities. Furthermore, people-oriented urbanization calls for public participation and stakeholder engagement in the planning process. This book brings together planners, designers, scholars, scientists, and government officials from China and all over the world to exchange ideas on urban regeneration.